Management of the Low-Flow Head and Neck Vascular Malformations in Children: the Sclerotherapy Protocol - Leung, Michael; Leung, Ling; Fung, Dickson; Poon, Wai-lun; Liu, Clarence; Chung, Kenneth; Tang, Paula; Tse, Sunny; Fan, Tsz-wo; Chao, Nicholas; Liu, Kelvin (European Journal of Pediatric Surgery, 2014)
Aim Image-guided sclerotherapy is becoming the preferred treatment for low-flow vascular malformations in head and neck region. The authors review the management protocol for this condition and evaluate its clinical outcomes.Methods Children with low-flow vascular malformations in head and neck region undergoing sclerotherapy from 2010 to 2013 were reviewed. All patients were assessed by pediatric surgeons and interventional radiologists in the multidisciplinary vascular anomalies clinic. Ultrasonography and intravenous contrast enhanced magnetic resonance imaging were performed preoperatively. Under general anesthesia with endotracheal intubation, sclerotherapy were performed with ultrasonographic and fluoroscopic guidance. Sodium tetradecryl sulfate (STS) foam or ethanolamine was used for venous malformation and doxycycline for lymphatic malformations as primary sclerosants, whereas 98% ethanol was reserved as an adjuvant sclerosant in selected cases of repeated procedures. Perioperative dexamethasone 0.2 mg/kg thrice daily was administered to decrease postsclerotherapy swelling and single dose intravenous mannitol 0.5 g/kg was given to minimize thromboembolic complications. Postoperatively, patients were admitted to intensive care unit for mechanical ventilation under deep sedation for airway protection.Results Overall 13 children (8 male and 5 female) with a mean age of 25 months (range, 2 mo–11 y) underwent a total of 25 sessions of image-guided staged sclerotherapy. There were five venous and eight lymphatic malformations. Location wise there were eight cervical, one lingual, one parotid, one lip, one facial, and one palatal lesions. Six patients had obstructive airway symptoms. Five patients required staged sclerotherapies from two to six sessions. There were no airway and thromboembolic complications. One patient had bleeding while another had recurrent swelling following sclerotherapy for lymphatic malformations and they were treated by aspiration. Significant size reductions of more than 50% volume were achieved in all patients. All patients with obstructive symptoms showed improvement.Conclusion Sclerotherapy is a safe and effective treatment for head and neck vascular malformations in children. Routine perioperative protocol is essential to reduce airway and thromboembolic complications. Size reduction and functional improvement occurred in all patients undergoing sclerotherapy.
Keywords: vascular malformations; head and neck; sclerotherapy